A Descriptive Study On Teaching Writing To The Eighth Grade Students At SMP Muhammadiyah 1 Pati In 2014/2015 Academic Year - NUGROHO WICAKSONO, SEPTIAN (2016)
SUMMARY Septian Nugroho Wicaksono. A320110045. A DESCRIPTIVE STUDY ON TEACHING WRITING TO THE EIGHTH GRADE STUDENTS AT SMP MUHAMMADIYAH 1 PATI IN 2014/2015 ACADEMIC YEAR. Research Paper. Muhammadiyah University of Surakarta. 2015. This research is aimed at observing teaching writing of English at SMP Muhammadiyah 1 Pati in 2014/2015 academic year. The objectives of the study are to describe the process of teaching writing, to describe objective of teaching writing, to describe the materials of teaching writing, to describe approach used by the teacher, and to describe the problems faced by the teacher in teaching writing at SMP Muhammadiyah 1 Pati. The type of the study is descriptive qualitative research especially naturalistic approach. In this research, the data are derived from event, informant, and field note. There are three techniques of collecting data, namely: observation, interview and documentation. The techniques for analyzing data are reduction of the data, display of data, and conclusion or verification. The results of the study are: (1) The describe the process of teaching learning writing. The process of teaching writing consists of opening, core-learning, and closing. In every meeting the teacher gives homework to the students to master the materials better and gives some information about material that would be learned next meeting. (2) The objectives of teaching writing at SMP Muhammadiyah 1 Pati are to make students understand and remember about the lesson and to develop communicative competence of the students in four language skills and one of them in writing. (3) The materials used by the teacher and students are appropriate with the syllabus of junior high school especially at eighth grade. The materials in teaching writing is recount text and used workbook entitled "Effective English" as handbook and "Headway English" as students' workbook. (4) The approaches applied by the teacher in teaching writing at eighth grade students are Product-based approach and Process-based approach. (5) The problem faced by the teacher in teaching writing are class management, limited time, different capability of the students, and unstable motivation of the students. Keywords: teaching writing, teaching learning writing, learning English